Benign mature teratoma of the conus medullaris in a 57-year-old-female: case report and literature review - Daniel Yamba Yamba; Dramane Cissé; Oualid Mohammed Hmamouche; Faycal Lakhdar; Mohammed Benzagmout; Khalid Chakour; Mohammed El Faiz Chaoui (Egyptian Journal of Neurosurgery)
Abstract Background The diagnosis of a mature teratoma in the conus medullaris is extremely rare, and few cases are reported in the literature. Case presentation We present a case of a 57-year-old woman who was referred from the neurology department for sudden weakness of the lower limbs. The patient has a medical history of chronic low back pain. She has normal bowel and bladder function. The neurological examination found reduced lower limb power, where the right and left proximal power were 0/5 and 2/5, respectively. Spinal cord MRI was performed, showing a well-delineated intramedullary mass at the level of the conus medullaris. Emergent surgery was performed using a surgical microscope, and the patient underwent a total resection of the tumor after T12–L2 bilateral laminectomy. The histological results were consistent with a benign mature teratoma and no additional postoperative neurological deficits were reported by the patient. Conclusion Adult’s cases of mature teratoma of the conus medullaris are extremely rare. The tumor present various symptoms primarily caused by compression, and definitive diagnosis is made by histological examination. Surgical excision is the most effective treatment, and total resection should be the aim. However, the surgical excision should be made under neurophysiological monitoring to avoid some injury to the surrounding neural tissue. Furthermore, the paucity of literature on the Adjuvant therapy for spinal teratoma is a challenge for neurosurgery for aiming of total resection.